2014
DOI: 10.1111/aor.12386
|View full text |Cite
|
Sign up to set email alerts
|

Survival Predictors in Ventricular Assist Device Patients With Prior Extracorporeal Life Support: Selecting Appropriate Candidates

Abstract: Several centers turn patients down for long-term ventricular assist devices (VADs) once they have received extracorporeal life support (ECLS) due to the expected poor outcome in these patients. The aim of this study was to identify survival predictors in this cohort of patients. Data of patients undergoing VAD support between January 2010 and November 2013 were retrospectively reviewed. Patients on ECLS support before implantation were considered eligible for inclusion. Outcome in survivors following long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…The period of ECLS stabilization and normalization of end-organ dysfunction may also explain why the model for end-stage liver disease (MELD) scores showed no differences between groups. We also found no correlation between the MELD score and survival, unlike other groups who found a pre-VAD MELD score of >25 to be predictive of poorer survival (6).…”
Section: Discussioncontrasting
confidence: 95%
“…The period of ECLS stabilization and normalization of end-organ dysfunction may also explain why the model for end-stage liver disease (MELD) scores showed no differences between groups. We also found no correlation between the MELD score and survival, unlike other groups who found a pre-VAD MELD score of >25 to be predictive of poorer survival (6).…”
Section: Discussioncontrasting
confidence: 95%
“…Several studies found that E-CPR in acute MI patients with CS and cardiac arrest resulted in acceptable survival rates and improved outcomes [71,[168][169][170]. Nonetheless, prior-ECMO support in patients with VAD was associated with postoperative complications especially RV and respiratory failure [172]. Finally, combining IABP with VA-ECMO is gaining more interest and has been associated with successful VA-ECMO weaning and improved mortality rates [173].…”
Section: Nonpharmacologic Circulatory Supportmentioning
confidence: 99%
“…Modern percutaneous approaches have resulted in wider utilization of ECMO, including in-hospital based programs that place patients in cardiac arrest on ECMO support (extracorporeal cardiopulmonary resuscitation [eCPR]), delivery programs with ‘in the field’ ECMO cannulation, and periprocedural ECMO in cardiac catheterization laboratories, in the surgical room and in the ICU [47]. Distal perfusion catheters that direct a proportion of the returned oxygenated blood flow from the ECMO circuit to the cannulated leg decrease the risks of critical limb ischemia in femoral cannulation.…”
Section: Management Of Cardiogenic Shockmentioning
confidence: 99%